2007
DOI: 10.1016/j.polymer.2007.01.032
|View full text |Cite
|
Sign up to set email alerts
|

Interaction between poly(vinyl pyridine) and poly(2,6-dimethyl-1,4-phenylene oxide): A copolymer blend miscibility study

Abstract: The phase behavior of blends of poly(2,6-dimethyl-1,4-phenylene oxide) (PPO) with random copolymers of styrene and 2-vinyl pyridine, Poly(S-co-2VP), as well as with random copolymers of styrene and 4-vinyl pyridine, Poly(S-co-4VP), has been investigated in order to estimate the values of the FloryeHuggins parameters c PPO;2VP and c PPO;4VP between PPO and 2-vinyl pyridine, resp. 4-vinyl pyridine. Using previously estimated values for the FloryeHuggins parameters 0:09 < c S;2VP < 0:11 and 0:30 < c S;4VP < 0:35,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 43 publications
1
5
0
Order By: Relevance
“…These values are close to but slightly greater than the expected c FH_crit value of 0.5. This finding is in agreement with other studies that have shown experimentally that the value of c FH_crit can vary depending on the nature and properties of the binary mixture (53,57,60,(75)(76)(77).…”
Section: Evaluation Of the Degree Of Interaction Within The Binary MIsupporting
confidence: 93%
“…These values are close to but slightly greater than the expected c FH_crit value of 0.5. This finding is in agreement with other studies that have shown experimentally that the value of c FH_crit can vary depending on the nature and properties of the binary mixture (53,57,60,(75)(76)(77).…”
Section: Evaluation Of the Degree Of Interaction Within The Binary MIsupporting
confidence: 93%
“…A recent study on the miscibility of random copolymers of styrene and 4-vinylpyridine, P(S-rand-4VP), with PPE showed that the interaction between PPE and P4VP is even more unfavorable than that between PS and P4VP. 37 From a similar miscibility study on blends of P(S-rand-4VP) and PS the Flory-Huggins parameter of the latter was found to satisfy 0.30 < χ S,4VP e 0.35. 38 The PDP-containing systems, except for one, involve the highly asymmetric diblock copolymer P103-S4VP (M n (PS) ) 19 600, M n (P4VP) ) 5100) in order that the weight fraction of the P4VP(PDP) block of the PS-b-P4VP(PDP) supramolecules is ∼0.5 (see Table 1).…”
Section: Resultsmentioning
confidence: 91%
“…15 More recently, Ten Brinke and coworkers have demonstrated using mean-field theory that v is close to 0.3-0.35, reflecting that the presence of strong repulsion interactions occurred between unlike species. 16 The aim of this article is to explore the miscibility in binary blends by means of DSC, FTIR, and TGA. First, we examined in detail by DSC technique the phase behavior of blends of poly(styrene-co-methacrylic acid)/Poly(styrene-co-4-vinylpyridine).…”
Section: Introductionmentioning
confidence: 99%